2010
DOI: 10.3390/rs2102369
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Green-Red Vegetation Index for Remote Sensing of Vegetation Phenology

Abstract: Abstract:We evaluated the use of the Green-Red Vegetation Index (GRVI) as a phenological indicator based on multiyear stand-level observations of spectral reflectance and phenology at several representative ecosystems in Japan. The results showed the relationships between GRVI values and the seasonal change of vegetation and ground surface with high temporal resolution. We found that GRVI has the following advantages as a phenological indicator: (1) "GRVI = 0" can be a site-independent single threshold for det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
289
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 433 publications
(304 citation statements)
references
References 26 publications
10
289
1
4
Order By: Relevance
“…Compared with the date of start of green up, the date of end of senescence was less certain. This concurs with other studies (using satellite data) that suggest it is more challenging to measure this as a single date [44] but that this can be overcome using a different index of the data (e.g., green-red vegetation index (GRVI) [45]). In order to fully understand why there was error in the predicted dates the values of greenness would need disaggregating to the component vegetation types and further research into different methods of data smoothing and date extraction would be required (similar to that applied to satellite data [29,46]).…”
Section: Computed Phenological Datessupporting
confidence: 75%
See 2 more Smart Citations
“…Compared with the date of start of green up, the date of end of senescence was less certain. This concurs with other studies (using satellite data) that suggest it is more challenging to measure this as a single date [44] but that this can be overcome using a different index of the data (e.g., green-red vegetation index (GRVI) [45]). In order to fully understand why there was error in the predicted dates the values of greenness would need disaggregating to the component vegetation types and further research into different methods of data smoothing and date extraction would be required (similar to that applied to satellite data [29,46]).…”
Section: Computed Phenological Datessupporting
confidence: 75%
“…Although further work is to be conducted using this network of cameras, this study joins others who have used cameras to capture leaf emergence and green-up (e.g., [34,50,53]) as well as senescence (e.g., [36,50]). Such studies point to the possibility of using other combinations of spectral channels (e.g., Zhao et [45]). Other suggested research avenues include a focus on understorey vegetation [16,61], though this would not be directly applicable using this network, though at different times of year the leaf area of certain trees may allow "background" vegetation to be observed [48,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ren et al (2014) found that trial-and-error threshold-based estimation was comparable to that of Win-CAM classification and was more efficient than WinCAM. In addition to the EGI-based threshold method, we also tried green relative vegetation index (GRVI = (G-R)/(G + R); Motohka et al, 2010). We did not try the normalized difference vegetation index (NDVI = (NIR-R)/(NIR + R), where NIR is near infrared band), due to lack of NIR band in a common camera.…”
Section: Image Analysismentioning
confidence: 99%
“…Therefore, an orthophoto mosaic with R, G, and B bands was used to compute RGB indices for the delineation of crop and soil pixels [32]. The Red-Green index [53,54] was computed using DN values (unsigned integer) to classify the crop and bare ground pixels. The output index values ranged between −1.0 to +1.0.…”
Section: Vegetation Indices and Bare Ground Pixel Extractionmentioning
confidence: 99%